Students’ Perception of Blended Learning in Intensive and Extensive Reading Classes at PSDKU MBD English Education Study Program of Pattimura University - Samloy, Marcel; Lekawael, Rosina F. J.; Anaktototy, Karolis (Prodi Pendidikan Bahasa Inggris, Program Studi Diluar Kampus Utama (PSDKU) Unpatti-MBD, 2021)
This study employed a survey design that focused on gather the data about how do the students perceive blended learning during the activities in two reading classes namely, Intensive reading and extensive reading. Challenges in implementing Blended Learning in both classes are identified. In order to collect the data to achieve the objective, the researchers utilized two instruments namely questionnaire and interview. The results of the questionnaire show that students have positive opinion and good perception toward the implementation of Blended Learning Method and it was supported by the data of the interview. During the learning process, students mostly faced troubles regarding their capability to operate particular online learning application. As much as fifty one percent of the students were identified to have limited online operation skill. Lack of gadgetry and limited supporting technological tools in them. About sixty percent of these students experienced this condition. Additionally, instability of internet connection in their respected places put all the students in troublesome situation. All the students agreed that bad internet connection was the most complicated part of conducting online learning process. This current study also addresses some alternatives proposed by both students and lecturers in order to overcome the existing problems and minimize the risk of ineffective online learning, particularly in Intensive and Extensive Reading classes at English Department of PSDKU MBD.